Pollen micromorphology and ultrastructure on four genera from Asphodelaceae and their taxonomical implication - Heidarian, Mehdi; Masoumi, Seyed-Mohammad; Fallah, Fahimeh (Phytotaxa, 2022)
Nine species from genera including Aloe, Asphodelus, Eremurus, and Hemerocallis (from subfamilies Asphodeloideae and Hemerocallidoideae) were examined by LM (Light Microscopy) and SEM (Scanning Electron Microscopy). Moreover, two species from Aloe and Eremurus were selected (Aloe vera and Eremurus spectabilis) and examined by TEM (Transmission Electron Microscopy). Our results showed that some qualitative (exine ornamentation from central and distal regions of the pollen grains and sulcus margin exine ornamentation) and all quantitative characteristics were varied. Dendrogram of the palynological characteristics constructed three pollen types (type 1 or Eremurus-Aloe type, type 2 or Asphodelus type, and type 3 or Hemerocallis type) that partly supported the genera level of the cladogram resulted from recent phylogenetical research and taxonomical issues. Also, the situation of subgenera from Eremurus was heterogenous in the palynological dendrogram. The studied species of Aloe and Eremurus were placed in type 1. The ultrastructure data, such as sporoderm thickness and number of intine layers in the sulcus margin region provided a better resolution for their differentiation from two selected species of these genera.